2013
DOI: 10.1080/09537325.2013.843664
|View full text |Cite
|
Sign up to set email alerts
|

Bioeconomy and the global economy: industrial policies and bio-innovation

Abstract: The last decades have witnessed major growth in the bioeconomy. Emergence of the bioeconomy as a broad, creative and rapidly expanding part of the global economy coincides with the maturation of the established drug discovery system. This paper presents research evidence focused on the relationships between changes in the bioeconomy and changes in the global economy. It argues that new forms of governance and regulation are key to strengthen industrial policies needed for emerging and developing countries to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…Also regions specialised in high-quality public research related to bio-technology may benefit in developmental terms [41]. It is furthermore suggested that connections between these global bio-technology centres are very important for innovation in the bioeconomy and that certain regions in emerging and developing economies may also take advantage of the bioeconomy [8,42]. As a consequence of the focus on global competition in the bioeconomy, the notion of governance of innovation also constitutes a central feature in some of the research underpinning such a vision [43,44].…”
Section: The Bio-technology Visionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also regions specialised in high-quality public research related to bio-technology may benefit in developmental terms [41]. It is furthermore suggested that connections between these global bio-technology centres are very important for innovation in the bioeconomy and that certain regions in emerging and developing economies may also take advantage of the bioeconomy [8,42]. As a consequence of the focus on global competition in the bioeconomy, the notion of governance of innovation also constitutes a central feature in some of the research underpinning such a vision [43,44].…”
Section: The Bio-technology Visionmentioning
confidence: 99%
“…For instance, the conceptualisations of the bioeconomy range from one that is closely connected to the increasing use of bio-technology across sectors, e.g., [8], to one where the focus is on the use of biological material, e.g., [9]. Thus, describing the bioeconomy, it has been argued that "its meaning still seems in a flux" [6] (p. 386) and that the bioeconomy can be characterised as a "master narrative" [10] (p. 95), which is open for very different interpretations.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear, for example, that big pharma requires a wide range of science, clinical trial, and other outsourced producers. Wield, 2013;Rafols et al, 2014;Mittra, 2016). On occasion, openness allows significant power to be devolved to multiple actors, even though the stronger (usually big pharma) partner can capture more value from collaborations (Gambardella and Panico, 2014).…”
Section: Specificity Of the Life Sciencesmentioning
confidence: 99%
“…Malerba (2002) mapped out four areas for future research, each of which we researched for the life sciences. First, progress in understanding of firm heterogeneity, structure and change within sectors, and on the role of sectoral institutions which we have mapped (Chataway et al, 2004;Orsenigo and Tait, 2008;Wield 2013). We have also built understanding of barriers to entry and the impact of regulatory systems on the lengthy clinical trials process which are important for Malerba's second and third areas of future research: the need for taxonomies of sectors; and research on the relationships between elements of a sectoral system (eg Mittra and Williams, 2007;Orsenigo and Tait, 2008).…”
Section: Sectoral Approaches To the Life Sciencesmentioning
confidence: 99%
See 1 more Smart Citation